School Health, Nutrition and HIV & AIDS: Policy - Guyana. Ministry of Education (Ministry of Education, Guyana, 2019)
The aim of this School Health and Nutrition and HIV Prevention Policy (hereafter referred to as "The Policy") is to promote and facilitate the implementation of health and nutrition programming and HIV Prevention throughout the education sector in Guyana. The most important principle that has guided the formation of this policy is the goal of Education for All. In the context of that goal, all education sector efforts towards improving school health, nutrition and HIV prevention are understood to stand squarely within the aim of the Government of Guyana that all children shall receive an education of quality.
Keywords: school health; school nutrition; HIV & AIDS